(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
During pregnancy, there is an increase in the need for nutrients to support the process of fetal growth and development. Sausage is a type of processed food which is popular and has high demand by the consumer. The purpose of this study was to develop sausage from mackerel fish and moringa leaf flour as protein and iron source for pregnant women. This study used completely randomized design with three formulas consisting of different combinations of mackerel and moringa leaf, namely F1 (100:0), F2 (90:10), and F3 (80:20). The samples were analyzed with sensory test (rating preference test and attribute difference test), physical analysis (texture and color) and nutrient analysis (proximate, calcium and iron). The results of this study indicated that an increase in moringa leaf flour used in the sausage formulation could reduce panelists’ acceptance for the attributes of color, aroma, texture, taste and overall acceptance. The increased use of moringa leaf flour also resulted in increased ash, protein, and carbohydrate contents and decreased water and fat contents. The selected formula was F2 with 10% moringa leaf flour which contained 17.80 g protein, 100.84 mg calcium and 6.52 mg iron per 100 g. One serving size of the sausage (74 g) contributes 7.8-8.2 of energy needs based on the Indonesian Recommended Dietary Allowance for pregnant women in the 1st to 3rd trimesters and it qualifies for the protein source and iron source claims.